2022
DOI: 10.3390/jcm11195662
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Emergency Room Visits and Rehospitalization for Bleeding Complications following Transurethral Procedures for the Treatment of Benign Prostatic Hyperplasia: A Population-Based Retrospective Cohort Study

Abstract: Background: The postoperative bleeding complications associated with laser surgery of the prostate and transurethral resection of the prostate (TURP) were compared. Methods: We used the Taiwan National Health Insurance Research Database to conduct an observational population-based cohort study. All eligible patients who received transurethral procedures between January 2015 and September 2018 were enrolled. Patients who received laser surgery or TURP were matched at a ratio of 1:1 by using propensity score mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In most studies, re-catheterization rates are about 10-12%, which is a composite of both middle and elderly patients. [ 24 , 25 ] The need for re-catheterization is mostly due to bleeding or urinary retention. [ 11 , 19 , 24 , 25 ] This is similar to our findings in this cohort of 41 elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies, re-catheterization rates are about 10-12%, which is a composite of both middle and elderly patients. [ 24 , 25 ] The need for re-catheterization is mostly due to bleeding or urinary retention. [ 11 , 19 , 24 , 25 ] This is similar to our findings in this cohort of 41 elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 , 25 ] The need for re-catheterization is mostly due to bleeding or urinary retention. [ 11 , 19 , 24 , 25 ] This is similar to our findings in this cohort of 41 elderly patients. In a review of 379 consecutive transurethral resections of the prostate, Reynard et al found 10% presented with an inability to void after catheter removal.…”
Section: Discussionmentioning
confidence: 99%
“…While TURP is considered to be the gold standard of relieving obstruction, it can have complications. A population-based, retrospective cohort study from Taiwan has compared the incidence of emergency room visits and rehospitalization for bleeding complications following TURP or laser-based transurethral procedures for the treatment of BPH [ 17 ]. Using data from the Taiwan National Health Insurance Research Data Base, propensity score matching, and applying a multiple regression analysis, they looked at 1651 patients each receiving laser or TURP treatment between January 2015 and September 2018.…”
Section: Studies On Treatment In Functional Urologymentioning
confidence: 99%
“…In the context of BPH laser surgery, Chen S-L and colleagues [ 7 ] performed an observational population-based retrospective study evaluating the postoperative bleeding complications among common six laser transurethral techniques and TURP (monopolar or bipolar) using the Taiwan National Health Insurance Research Database. While GreenLight photovaporization (PVP) and thulium laser vaporesection (ThuVARP) of the prostate were associated with a lower incidence of bleeding events and clot retention compared to monopolar TURP, even in patients receiving anticoagulant or antiplatelet therapy, diode laser enucleation (DiLEP) and holmium laser enucleation (HoLEP) did not result in fewer bleeding events than monopolar TURP.…”
mentioning
confidence: 99%